Challenges and opportunities in goat commercialization and industry in the ASEAN region (for viability and sustainability) - Ramli, Abdullah; Wan Khadijah, Wan Embong; Ahmad Zubaidi, Abdul Latiff (2019)
The population of goat globally is around 1 billion head, mainly in Asia. Goats are reared traditionally by smallholders with low productivity, lack of technology and poor management for meat and milk production for their livelihood. In the Asean region, goat production is gaining popularity, particularly in Indonesia, Philippines, Thailand, Malaysia and Vietnam. Goat meat can be eaten by all human population of the world without restriction to religion, culture and social prohibition. Therefore, Asean countries should capitalize on this opportunity to promote goat industry and commercialization not only for the wellbeing of the small farmers but also as a niche for income generation as well as for food security and safety for the stakeholder's countries in Asean. However, some pertinent challenges and constraints which include the improvement of adaptable goat breeds with superior meat and milk production, improve GAHP, control of diseases, viable and sustainable strategic development program, government policy, feed improvement, human capital development program, socio-cultural practices and good marketing strategies, inter alia, must holistically be addressed first. It is possible that in the near future Asean will be the goat commercialization and industry hub globally in- line with the progress of other livestock animals such as cattle, sheep, swine and poultry.